Exploring the differences in mortality and its associated factors among young-old and old-old COVID-19 patients - Linyi Zhong; Linyi Zhong; Linlin Huang; Mengchen Zhang; Congcong Tian; Lijuan Zhang; Guobin Song (Frontiers in Medicine, 2025)
BackgroundThis study aims to compare the differences in mortality and related factors between old-old and young-old COVID-19 patients and find unique factors related to survival in old-old patients.Study designSingle-center retrospective cohort study following STROBE guidelines.MethodsWe included 302 elderly (≥65 years old) COVID-19 patients admitted to Shijiazhuang People’s Hospital from December 1, 2022 to March 31, 2023. Among them, 142 were assigned to the young-old group (65–74 years old) and 160 in the old-old group (≥75 years old). Demographic, clinical and laboratory data were extracted, and descriptive statistical analysis, comparison of differences between groups, Cox proportional hazards regression analysis, and subgroup analysis were adopted.ResultsCompared with the young-old group, the mortality of old-old patients was higher (31.3% vs. 12.7%, p < 0.001). Risk factors associated with mortality specifically in old-old patients include dyspnea (HR: 2.829, 95%CI: 1.571–5.093), acute cardiac injury (HR: 2.403, 95%CI: 1.369–4.219), and diabetes (HR: 2.401, 95%CI: 1.311–4.397), glucocorticoid therapy (HR: 2.397, 95%CI: 1.198–4.798). Moreover, there was a significant difference in the survival curves between the young-old and the old-old group (p = 0.0001). However, no significant sex differences in mortality and survival curves were found in either group.ConclusionThis study found for the first time that dyspnea symptoms, acute heart injury, diabetes, and glucocorticoid therapy are unique risk factors related to survival in old-old patients with COVID-19. These factors need more attention when treating old-old patients to prevent poor prognosis.